IMPLEMENTASI METODE FINITE STATE AUTOMATA PADA SCREENING AWAL PENERIMAAN PEGAWAI - Annisa Novtariany; Windu Gata; Enie Heni Hermalani; Sri Rahayu; Hafifah Bella Nofitasari (JURNAL ILMIAH INFORMATIKA, 2022)
Every company always has a recruitment selection process with the hope that the company can get competent employees. The selection process usually has several criteria that are usually predetermined by the company which are needed in the initial selection process for hiring employees. Thus it is necessary for an application system that can carry out the initial screening process for employee recruitment to assist the implementation of the selection process. The design of this application uses the FSA implementation with the NFA type as an abstract machine to determine the stages and transitions contained in these stages which are used to determine the results of the initial screening of employee recruitment. If they meet the specified criteria, they will pass at this stage. This is a role in making abstract machines for the initial screening process for employee recruitment using Nondeterministic Finite Automata (NFA) because each stage can lead to several stages at once.